Effect of heart rate variability biofeedback training on score and stress level of shooting athletes - Donghai, Huang; Muhammad Nubli, Abdul Wahab; Xiuling, Zhang (e-International Publishing House, 2024)
This study aimed to explore the impact of a 12-week emWave pro-based heart rate variability biofeedback training followed by a 2-week follow-up on shooters' performance, stress levels, and heart rate variability (HRV). Thirty-six shooters aged 18-24 (18 experimental, 18 control) participated. The experimental group underwent 12 weeks of biofeedback and shooting training, while the control group only received shooting training. Results showed significant improvements in performance, stress levels, and HRV parameters in the experimental group, reflecting enhanced parasympathetic activity. Biofeedback reduced training and competition stress, improving overall performance and stability during matches, emphasizing its effectiveness in shooter training.